Penggunaan Bahasa Formal dan Informal Dalam Komunikasi Email Bisnis Sekretaris di Era Digital - Maria Estri Wahyuningsih; Lucia Yeni Wijayatri; Agnes Sobalisa (Jurnal Administrasi dan Kesekretarisan, 2026)
This study on the use of formal and informal language in secretarial business email communications aims to determine the effectiveness of formal and informal language use in secretarial business email communications. This study used a qualitative descriptive method. The results have implications for the development of secretarial professional competencies. Secretaries need a good understanding of the principles of formal business communication to compose professional and effective emails. Secretaries also need to understand the dynamics of digital communication, which allows for more flexible language use. Secretaries are able to use language in business communications in the era of globalization.